2008
DOI: 10.1111/j.1423-0410.2008.01060.x
|View full text |Cite
|
Sign up to set email alerts
|

Toxicity related to autologous peripheral blood haematopoietic progenitor cell infusion is associated with number of granulocytes in graft, gender and diagnosis of multiple myeloma

Abstract: Our results indicate that beside the infused DMSO dose, the composition of graft as well as patient's diagnosis are also very important factors for infusion-related toxicity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
36
0
1

Year Published

2010
2010
2012
2012

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 21 publications
(42 citation statements)
references
References 9 publications
5
36
0
1
Order By: Relevance
“…It is possible that factors predisposing to poor mobilization and/or correlating with pre-transplant co-morbidity profiles, especially cardiovascular disease or infections might also predispose a patient to more severe infusion-related toxicity. Age, gender and patient diagnosis have been reported as predictors of AEs in other studies (4, 8, 17). Bojanic et al identified female gender and diagnosis of multiple myeloma in addition to granulocyte content as factors predicting infusion-related toxicity(4).…”
Section: Discussionmentioning
confidence: 65%
See 3 more Smart Citations
“…It is possible that factors predisposing to poor mobilization and/or correlating with pre-transplant co-morbidity profiles, especially cardiovascular disease or infections might also predispose a patient to more severe infusion-related toxicity. Age, gender and patient diagnosis have been reported as predictors of AEs in other studies (4, 8, 17). Bojanic et al identified female gender and diagnosis of multiple myeloma in addition to granulocyte content as factors predicting infusion-related toxicity(4).…”
Section: Discussionmentioning
confidence: 65%
“…Age, gender and patient diagnosis have been reported as predictors of AEs in other studies (4, 8, 17). Bojanic et al identified female gender and diagnosis of multiple myeloma in addition to granulocyte content as factors predicting infusion-related toxicity(4). The effect of age is not so clear as Milone et al reported increasing incidence of AEs with increasing age(8) whereas Cordoba et al found increased age to be protective against occurrence of AEs(17).…”
Section: Discussionmentioning
confidence: 65%
See 2 more Smart Citations
“…In addition, Milone et al reported noncardiovascular AEs were dependant on patient age and the concentration of nonmononuclear white blood cells in the infused HPC product [2]. Bojanic et al reported toxicity of autologous HPC infusions was associated with the number of granulocytes in the graft, gender, and diagnosis of multiple myeloma [3]. The only cells that survive the freezing process are MNC; so cellular debris from ruptured RBC, PLT, and granulocytes are infused into the patient.…”
Section: Introductionmentioning
confidence: 97%